Modeling post-socialist urbanization. The case of Budapest. - Kiss, Daniel (Birkhäuser, 2019)
Thema des Buches ist die postsozialistische Stadtentwicklung, -planung und -regierung von Budapest zwischen 1990 und 2010. Der Autor konstatiert für diese Zeit eine Schwäche der kommunalen Planung. Dies habe dazu geführt, dass große Investitionsprojekte ohne Koordination und übergeordnete Planung verlaufen seien. Der Verfasser konstruiert ein Modell, dass aus drei Narrativen besteht: "Socialist Urban Legacy Narrative", "Decentralization Narrative" und "Kulturkampf-Narrative". Jede dieser Narrativen sieht er als Verbindung zwischen dem historischen Hintergrund und der jüngeren Entwicklung der Stadt, die er zudem als beispielhaft für die Entwicklung postsozialistischer Städte erachtet.

The author examines the urban development of Budapest from 1990 to 2010. This period is characterized by the significant decline in communally town planning: given the structural legacies of socialist urbanization, the decentralization of government and resources, and the impact of a post-socialist culture struggle, a trend is being analyzed in which nebulous competencies lead to unclear and thus to a failure of higher-level planning. The ensuing consequence is an increase in large, investment-driven projects: it is characteristic of these privately financed projects that they do not submit to higher level control, in particular when these control bodies are rather weak. This model-based analysis presents the phenomenon as exemplary of the development in post-socialist cities.
Keywords: Stadtentwicklung; Großstadt; Hauptstadt; Stadtplanung; Entwicklungssteuerung; Urbanisierung; Transformation; Stadtwachstum; Strukturwandel; Gesellschaftlicher Wandel; Privatinvestition; Investitionsklima; Bauwirtschaft; Dezentralisierung; Governance; Stadtsoziologie; Regionale Identität; Postsozialismus